Pleasing or fighting future tastes? Projection bias versus conflict of selves - Sebastian Krügel; Matthias Uhl (Philipps-University Marburg, School of Business and Economics, 2016)
Many real life choices concern consumption in future periods. Previous studies apparently demonstrate that people systematically mispredict future tastes in such situations. This evidence, however, is also consistent with the idea that people understand, but do not approve of their future tastes. To disentangle both approaches, we conducted a framed field experiment with commitment option. In our experiment, commitment was not a device against weak will. It was a judgment which a planner imposed on another planner. The results suggest that people do not always aim to please future tastes. People may sometimes experience a conflict between two far-sighted selves.
Keywords: C93; D03; D90; 330; State-dependent preferences; Empathy gap; Multiple selves; Commitment; Intrapersonal conflict